2015
DOI: 10.1002/mawe.201500402
|View full text |Cite
|
Sign up to set email alerts
|

Transient liquid phase bonding of AA 6082 aluminium alloy

Abstract: Transient liquid phase bonding (TLP) on AA 6082 samples were performed under ambient non‐vacuum conditions, which was possible by a suitable pre‐treatment. This treatment involves a zincate treatment followed by copper plating, which is a common industrial process and can be performed in large batches. This treatment allows to remove the natural aluminium oxide layer and to protect the aluminium surface from excessive oxidation. Different bonding conditions were investigated and showed the feasibility of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…EDS analyses on the foam surfaces evidenced the presence of C, O, Mg and Al on AF1 samples, and of C, O, Al and Si on the AF2 samples. Moreover, the AF1 samples showed numerous particles rich in O and Mg, attributable to the Mg-rich oxides and carbonates frequently observed on Al-Mg alloys [5][6][7]. These particles are hardly removed; only mechanical grinding can detach them from the surface.…”
Section: Resultsmentioning
confidence: 99%
“…EDS analyses on the foam surfaces evidenced the presence of C, O, Mg and Al on AF1 samples, and of C, O, Al and Si on the AF2 samples. Moreover, the AF1 samples showed numerous particles rich in O and Mg, attributable to the Mg-rich oxides and carbonates frequently observed on Al-Mg alloys [5][6][7]. These particles are hardly removed; only mechanical grinding can detach them from the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Contact reactive brazing is a kind of brazing method without any brazing flux [ 21 ], which has been widely applied for brazing Al alloys to other alloys, such as Al6063 [ 22 ], Al6061 to AZ31B Mg alloy [ 23 ], and Al6063 to 1Cr18Ni9Ti stainless steel [ 24 ]. Schällibaum et al [ 25 ] studied the microstructure of the AA6082 brazed joints with plating copper, and the results showed that the formation of defects was caused by the residual oxide films aggregated in the brazed joint. Wu et al [ 24 ] used Cu as an interlayer to join Al6063 and 1Cr18Ni9Ti stainless steel by contact reactive brazing.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main obstacles to the effective brazing of Al alloys is the presence of a stable oxide layer on the surface with high melting temperature and poor reactivity, which act as a barrier for metallurgical interaction between the aluminum alloy substrate and the brazing material [9,10]. Particularly critical from this point of view are the Al alloys of the 5000 series because of high magnesium content, which promotes the development of a thick and stable magnesium oxide layer.…”
Section: Introductionmentioning
confidence: 99%